LEGAL MALFUNCTIONS AND EFFORTS IN RECONSTRUCTING THE LEGAL SYSTEM SERVICE: A STATE ADMINISTRATIVE LAW PERSPECTIVE - Agustina, Enny (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Implementation of the state and its administration duties in a state of law recognizes written law in the constitution or the regulation as stated in the constitutional law. The constitutional law requires another law to implement technical issues, which is the state administrative law. This is a library re-search which aims to find out the malfunction of State Administrative Law as well as the attempt to reconstruct a solution for service law. To improve the given conditions, it requires reconstructing the legal system including legal structure, substance, and culture to change in the field of public service by restoring and providing service and to serve literally.Â Keywords: state administrative law, malfunctions.